Japan's international relations politics, economics, and security - Hook, Glenn D.; Gilson, Julie; Hughes, Christopher W.; Dobson, Hugo (Sheffield Centre for Japanese Studies/Routledge series, 2001)
This comprehensive and user-friendly textbook provides a single volume resource for all those studying Japan's international relations. The book offers a clear and concise introduction to the most important aspects of Japan's role in the globalized economy of the twenty-first century.